High resolution ultrasound in posterior interosseous nerve syndrome. Issue 1 (20th September 2013) - Djurdjevic, Tanja; Loizides, Alexander; Löscher, Wolfgang; Gruber, Hannes; Plaikner, Michaela; Peer, Siegfried
ABSTRACT Introduction: Posterior interosseous nerve (PIN) syndrome is a rare compression neuropathy of the PIN in the region of the supinator muscle, most common by the arcade of Frohse. We aimed to specify ultrasonographic findings in patients with PIN syndrome in comparison to healthy volunteers. Methods: Ultrasound images and clinical data of 13 patients with PIN syndrome confirmed by neurological examination and electrophysiological testing were evaluated retrospectively. Anteroposterior nerve diameters measured at the arcade of Frohse were compared with those of 20 healthy volunteers. The echotexture and the presence of a caliber change of the PIN were additionally assessed. Results: Enlargement of the PIN was seen in all patients with PIN syndrome, but not in volunteers (statistically significant difference in mean diameter P < 0.05). Furthermore, edema and caliber change of the PIN were present in all patients. Conclusions: High‐resolution ultrasound allows for differentiation between patients with PIN syndrome and healthy volunteers. Muscle Nerve49: 35–39, 2014